Synthesis of Tris-Heterocycles via a Cascade IMCR/Aza Diels-Alder + CuAAC Strategy - Rentería-Gómez, Manuel A.; Islas-Jácome, Alejandro; Pharande, Shrikant G.; Vosburg, David A.; Gámez-Montaño, Rocío (Frontiers in Chemistry, 2019)
6-Triazolylmethyl-pyrrolo[3,4-b]pyridin-5-one tris-heterocycles were synthesized in 43-57% overall yields. The two-stage synthesis involved a cascade process (Ugi-3CR/aza Diels-Alder/N-acylation/aromatization) followed by a copper-assisted alkyne-azide [3+2] cycloaddition (CuAAC). This efficient and convergent strategy proceeded via complex terminal alkynes functionalized with a fused bis-heterocycle at the -position. The final products are ideal candidates for SAR studies as they possess two privileged scaffolds in medicinal chemistry: 1H-1,2,3-triazoles and pyrrolo[3,4-b]pyridin-5-ones.